Post-Pandemic Language Instruction for Indigenous Learners: A Phenomenological Inquiry in Kalamansig District, Southern Philippines - Obregon, Aprilyn; H. Boquia, Arbaya (International Journal of Linguistics and Translation Studies, 2025)
The study explored the experiences of English Language Teachers (ELTs) teaching tribal learners in a non-tribal high school in Kalamansig Municipality, Sultan Kudarat Province. Using a hermeneutic phenomenological approach, ten ELTs identified through the purposive sampling technique participated in an in-depth interview guided by a validated semi-structured questionnaire. Data analysis adhering to Colaizzi's (1978) process revealed that participants generally experienced Teachers' Enthusiasm and Learners' Politeness, Learners' Mismatch of Understanding Levels, and Adverse Teaching Environment. They faced challenges in Learners' Educational & Academic Skills, particularly limited vocabulary, low comprehension, and underdeveloped macro skills –speaking, reading, and writing, Learners' Participation, and Socio-economic and Cultural Factors such as Early Marriage & Pregnancy. They employed strategies such as Collaborative Learning, Use of Adaptive Teaching Strategies, and Anti-Discrimination Advocacy and Collaborations with the Community to address these. The study underscored that English Language Teachers' Patience and Flexibility are necessary qualities to be effective teachers to Tribal Learners.